The comorbidity of bipolar disorder and cardiovascular diseases from pharmacotherapy perspective - Vuksan-Ćusa, Bjanka (Array, 2009)
The heart and mind are intimately linked. Patients with severe mental disorders have increased mortality rates compared with the general population and the leading cause of premature death is cardiovascular disease (CVD). Despite their high prevalence and substantial medical impact, comorbidity between cardiac conditions and psychiatric illnesses frequently go undiagnosed and untreated. It is very interesting to investigate the impact of mental health on cardiac disease and what is the complex underlying mechanism that links theese two conditions